Corrosion inhibition of carbon steel in hydrochloric acid: Elucidating the performance of an imidazoline-based surfactant. (March 2021) - Kousar, K.; Walczak, M.S.; Ljungdahl, T.; Wetzel, A.; Oskarsson, H.; Restuccia, P.; Ahmad, E.A.; Harrison, N.M.; Lindsay, R.
Graphical abstract: Highlights: Excellent inhibition efficiency is achieved well below the CMC. XPS reveals interface chemistry as a function of corrosion inhibitor concentration. Cl 2p XPS line shape of atomic chlorine suggests presence of interface heterogeneity. No oxide or salt film is present on a well-inhibited carbon steel surface. Abstract: A combination of electrochemical measurement and interface analysis have been applied to characterise the interaction of OMID, an exemplar imidazoline-based corrosion inhibitor, with carbon steel in 1 M hydrochloric acid. Corrosion inhibition efficiency data indicate that excellent performance is achieved well below the critical micelle concentration. High resolution X-ray photoelectron spectra demonstrate that, as the corrosion rate decreases, the interface evolves towards one comprising OMID bound to film-free carbon steel. This latter result provides key input for those researchers attempting to predict corrosion inhibitor functionality through atomic scale interfacial modelling, and so identify next generation chemistries.